Artificial intelligence and audit quality: Implications for practicing accountants - Adeoye, Isaiah Oluwasegun; Akintoye, Rufus Ishola; Aguguom, Theophilus Anaekenwa; Olagunju, Olubusola Ayoola (Asian Economic and Financial Review, 2023)
Audit quality has been one of the most controversial issues in auditing and financial reporting research. The implication of audit quality has become critically significant for accountants and users of accounting information. Some studies have shown that the improvement of audit quality lies with the application of artificial intelligence in audit exercises. This study examines the effect of artificial intelligence on audit quality by employing the survey method, using structured questionnaires administered to practicing accountants and staff of the Big Four accounting firms. The Taro Yamani formula was used to determine the sample size, and a total of 641 questionnaires were retrieved. Cronbach’s alpha was employed to test the reliability and validity alongside the pilot testing conducted. Descriptive statistics and inferential analysis were also used. The results of the descriptive method showed that many of the respondents support the usefulness of artificial intelligence. The regression results revealed that artificial intelligence has a positive effect on audit quality. Based on the results, it is recommended that managers and accountants in private, corporate, and accounting firms should embrace the application of artificial intelligence due to its economic value and helpful effect of improving audit quality in terms of accuracy, reliability, and timely financial reporting.